Dynamic Characteristics of Rotating Stall in Mixed Flow Pump - Xiaojun Li; Shouqi Yuan; Zhongyong Pan; Yi Li; Wei Liu (Journal of Applied Mathematics)
Rotating stall, a phenomenon that causes flow instabilities and pressure hysteresis by propagating at some fraction of the impeller rotational speed, can occur in centrifugal impellers, mixed impellers, radial diffusers, or axial diffusers. Despite considerable efforts devoted to the study of rotating stall in pumps, the mechanics of this phenomenon are not sufficiently understood. The propagation mechanism and onset of rotating stall are not only affected by inlet flow but also by outlet flow as well as the pressure gradient in the flow passage. As such, the complexity of these concepts is not covered by the classical explanation. To bridge this research gap, the current study investigated prerotation generated at the upstream of the impeller, leakage flow at the tip clearance between the casing and the impeller, and strong reserve flow at the inlet of the diffuser. Understanding these areas will clarify the origin of the positive slope of the head-flow performance curve for a mixed flow pump. Nonuniform pressure distribution and adverse pressure gradient were also introduced to evaluate the onset and development of rotating stall within the diffuser.